Metabolic dysfunction-associated steatohepatitis is the leading indication for adult liver transplantation in Saudi Arabia - Saleh A. Alqahtani; Shadan AlMuhaidib; Dimitri A. Raptis; Waleed K. Al-Hamoudi; K. Rajender Reddy; Dieter C. Broering; Saad A. Alghamdi (PLoS ONE, 2025)
Background Liver transplantation (LT) represents the life-saving treatment for advanced liver disease. We aim to investigate LT indication trends and outcomes in Saudi Arabia, following the evolution of effective therapies for hepatitis C virus (HCV) and the rising fatty liver disease prevalence. Methods We retrospectively analyzed data from adult patients who underwent LT from 2011 to 2023 at a tertiary referral center in Saudi Arabia. We assessed demographics, LT indication trends, Model for End-stage Liver Disease (MELD) scores, donor type, and survival outcomes. Results A total of 1,419 patients were included. The median age was 56.9 years, with 37.4% female. Living donor LT (LDLT) represented 79.8% of all transplants, and 22.0% of recipients had hepatocellular carcinoma (HCC). Metabolic dysfunction-associated steatohepatitis (MASH) was the predominant indication for LT (33.2%), followed by HCV (18.0%) and hepatitis B virus (HBV) (17.1%). Overall survival rates at 1-, 2-, 3-, 5-, and 10-years post-transplantation were 87.9%, 85.0%, 82.4%, 77.7%, and 71.3%, respectively. Hazard ratios (HR) for mortality were lower in patients with HBV compared to MASH (HR: 0.44, 95% CI: 0.28–0.69, p < 0.001), and higher in patients aged ≥65 years (HR: 1.37, 95% CI: 1.02–1.84, p = 0.036), those with diabetes (HR: 1.33, 95% CI: 1.03–1.73, p = 0.029), and those with increased MELD score (HR: 1.02, 95% CI: 1.00–1.04, p = 0.022). LDLT was associated with reduced mortality risk (HR: 0.68, 95% CI: 0.51–0.92, p = 0.013). Conclusions MASH represents the leading indication for LT in this large cohort, necessitating preventive strategies and early detection efforts.